Frank Lloyd Wright - Burns, Ken, 1953-; Novick, Lynn.; Ward, Geoffrey C.; Miller, Peter, 1961-; Herrmann, Edward; Florentine Films; WETA-TV (Television station : Washington, D.C.); PBS Home Video; Paramount Home Entertainment (Firm) ([Alexandria, Va.] : PBS Home Video ; Hollywood, Calif. : Distributed by Paramount Home Entertainment, 2004)
Uses interviews and archival footage to tell the story of the melodramatic life and stunning architecture of Frank Lloyd Wright. Discusses some of the 800+ buildings designed by Wright, including the Guggenheim Museum, the Johnson Wax Building, Fallingwater, Unity Temple, and Taliesin. Examines how Wright's buildings and ideas changed the way we live, work, and see the world around us. Documents the turbulence of Wright's personal life, including his three marriages, financial troubles, and many scandals.
The fellowship -- Hosanna! A client! -- Just build me an office building -- I can't get them out fast enough -- I am immortal.
DVD.
Closed-captioned.
Narrator, Edward Herrmann; voices: Philip Bosco, Julie Harris, Sab Shimono.
Cinematography, Buddy Squires, Ken Burns ; editor, Tricia Reidy.
Originally broadcast on PBS in 1998.
Full screen presentation; Dolby surround stereo.
Keywords: Wright, Frank Lloyd, -- 1867-1959.; Wright, Frank Lloyd, -- 1867-1959 -- Family; Wright, Frank Lloyd, -- 1867-1959 -- Homes and haunts; Architects -- United States -- Biography; Architecture -- United States -- History -- 20th century; Prairie school (Architecture); Documentary television programs; Biographical television programs; Video recordings for hard of hearing people